#TITLE_ALTERNATIVE# - HISKIA PINEM (NIM 10101011), JAREN
In this paper, we observe the linear model of 1-D a fluid flow which is disturbed by a bump placed on the bottom of the channel. We solve the model numerically by the fourth order Runge-Kutta method to observe the effect of the parameter Froude number and the height of the bump. As we will see in this paper, numerical solution of the model produce three propagating wave.